An Introduction to Management Science - Parenteau, L.-René (Relations industrielles / Industrial Relations, 1968)
This article reviews "An Introduction to Management Science" by Teichroew Daniel.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z